(untitled) (Research, Society and Development, 2022)
Introduction: Drugs are becoming increasingly indispensable for the health of the population, since they have great relevance with regard to prevention, recovery and maintenance of the quality of life of individuals. However, the low-income population has its treatment impaired due to the high cost of many medications that are prescribed and, therefore, sometimes they do not start or are unable to continue what was proposed by the health professional. Objective: to understand more about the acceptance of generic drugs, and the challenges it faces in the pharmaceutical market. Methodology: this is an integrative literature review about the acceptance of generic drugs and their challenges in the pharmaceutical market. In order to carry out the article, an investigation was carried out on platforms and virtual research banks, specifically: Scientific Electronic Library Online (Scielo) and Virtual Health Library (BVS). Results and discussion: the PNM provided the population with greater access to medicines, allowing the Brazilian population to achieve a better quality of life. In view of the results, the importance of knowledge about the effectiveness and quality of generic drugs, the prescription of this by health professionals and the importance of pharmacists to facilitate the interchangeability between branded and generic medications was evident. Conclusion: with the present study it can be concluded that generic drugs are extremely important for drug treatments, especially when the cost of the reference drug is high, since generics have a lower price. However, the acceptance of these drugs by the public is not yet solidified and depends, mainly, on the indication of the health professional and on the knowledge about the properties and efficacy of generic drugs.